Development of methodology for analyzing travel patterns in the context of developing countries - Mabazza, Daniel L. (Philippine Engineering Journal)
Many cities in developing countries have been suffering from worsening traffic congestion and environmental degradation in city centers and most of radial corridors, which are caused by rapid urbanization trend and unbalanced transportation systems. Under such circumstances, this study attempts to develop a new methodology for 1) identifying representative travel patterns in developing countries based on a data mining approach called Exhaustive CHAID, and 2) clarifying the influential socio-economic attributes and/or mobility factors for the identified travel patterns by combining SEM (Structural Equation Modeling) approach and an aggregate-type logit model. The effectiveness of the methodology was confirmed based on the person-trip data obtained from "Metro Manila Urban Transport Integration Study" in 1996.